Evaluation of Efficacy and Safety of Oral Cyclosporine in the Treatment of Severe Alopecia Areata - Sahar A. Majeed1, Asmaa Abdul Jaleel Swadi2, Ekhlas Sabah Hassan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: One of common forms of scaring hair loss is alopecia. Alopecia is an autoimmune disorder that is characterized by relapsing and remitting episodes of non scaring hair loss. Several treatment options are nowadays available to be prescribed to patients with alopecia areata including local and systemic corticosteroid therapy, immune suppressant agents and contact immunotherapy. Nonetheless, none of these agents have been 100 % effective in eradication of the disease totally and some agents are associated with intolerable side effects. Therefore, dermatologists are continuously searching for new agents and modalities in order to get better response and less sided effects.Aim of the Study: The current study was planned and conducted to evaluate the efficacy and safety of oral cyclosporine in treating alopecia areata.Patients and Method: This study included 35 patients with alopecia areata. The study was conducted at the dermatology unit, Al-Diwaniyah Teaching Hospital, Al-Diwaniyah Province, Mid-Euphrates Region of Iraq. The study started on June the 2nd 2018 and extended to June the 2nd 2019. The study was approved by the institutional ethical approval committee and included a verbal consent was obtained from each participant following full demonstration of the aim and procedures of the study. Every patient has received a daily dose of oral cyclosporine (3 mg/kg) for a period in the range of 2 to 12 months. Variables included in the current study were age, gender, type of alopecia areata, duration of disease, duration of treatment and treatment response. Outcome in the end of the study included clinical response and main side effects.Results: Following treatment with oral cyclosporine, 28 patients (80 %) had satisfactory response and 7 patients (20 %) had unsatisfactory response. Treatment response was not correlated to age, gender, disease duration or type of disease (P > 0.05). There were unremarkable adverse effects in association with oral cyclosporine use.Conclusion: oral cyclosporine is effective and safe mode of treatment in patients with alopecia areata.